Microstructure Evolution and Magnetic Properties of a 4.5 wt% Silicon Steel Produced by Twin‐Roll Casting. Issue 11 (23rd September 2022) - Müller, Max; Bailly, David; Hirt, Gerhard
Abstract : Herein, an alloy with 4.5 wt% Si is produced by twin‐roll casting and processed into a crack‐free electrical steel by warm rolling and final annealing. A comprehensive material characterization allows insight into the solidification structure, Si segregation, the microstructure, and texture evolution during the process chain, as well as into the soft magnetic properties of the produced electrical steel. A weak but favorable θ ‐fiber is formed by twin‐roll casting and appears again in the final annealed state. Despite the high Si content, this leads to relatively high polarization values. Nevertheless, the expected low iron losses of the Fe–4.5Si alloy cannot be verified, which is probably related to impurities, insufficient flatness, and inhomogeneous grain size distribution. Abstract : An increase in the silicon content is expected to increase the efficiency of electrical steel sheets significantly. The environmentally friendly twin‐roll casting process can open up new windows in terms of achievable silicon content. Herein, the production chain from the twin‐roll casting process to a final annealed non‐grain‐oriented electrical steel with 4.5 wt% silicon is presented.